How Physical Factors Coordinate Virus Infection: A Perspective From Mechanobiology - Liu, Wei; Tang, Daijiao; Xu, Xin-Xin; Liu, Yan-Jun; Jiu, Yaming (Frontiers in Bioengineering and Biotechnology, 2021)
Pandemics caused by viruses have threatened lives of thousands of people. Understanding the complicated process of virus infection provides significantly directive implication to epidemic prevention and control. Viral infection is a complex and diverse process, and substantial studies have been complemented in exploring the biochemical and molecular interactions between viruses and hosts. However, the physical microenvironment where infections implement is often less considered, and the role of mechanobiology in viral infection remains elusive. Mechanobiology focuses on sensation, transduction and response to intracellular and extracellular physical factors by tissues, cells and extracellular matrix. The intracellular cytoskeleton and mechanosensors have been proved to be extensively involved in virus life cycle. Furthermore, innovative methods based on micro- and nanofabrication techniques are being utilized to control and modulate the physical and chemical cell microenvironment, and to explore how extracellular factors including stiffness, forces and topography regulate viral infection. Our current review covers how physical factors in microenvironment coordinate virus infection. Moreover, we will discuss how this knowledge can be harnessed in future research on cross-fields of mechanobiology and virology.